Prognostic Impact of Expression of Bcl-2 and Bax Genes in Circulating Immune Cells Derived from Patients with Head and Neck Carcinoma - Tano, Tomoyuki; Okamoto, Masato; Kan, Shin; Nakashiro, Koh-ichi; Shimodaira, Shigetaka; Koido, Shigeo; Homma, Sadamu; Sato, Mitsunobu; Fujita, Tomonobu; Kawakami, Yutaka; Hamakawa, Hiroyuki (Neoplasia (New York, N.Y.), 2013)
Antitumor functions of the host immune system are frequently compromised in patients with malignancies. In the current study, we evaluated the relationship between expression ratio of mRNAs for the antiapoptotic protein Bcl-2 and the proapoptotic protein Bax (the Bcl-2/Bax ratio) in peripheral blood mononuclear cells and clinical outcomes in patients with head and neck carcinomas. The overall survival (OS) time of patients with Bcl-2/Bax ratios ≥ 1.2 tended to be longer than that of patients with Bcl-2/Bax ratios < 1.2 but not significantly so (P = .084, n = 61). Disease-free survival (DFS) of patients with Bcl-2/Bax ratios ≥ 1.2 was statistically significantly longer than that of patients with Bcl-2/Bax ratios < 1.2 (P = .001, n = 76). All of the patients whose Bcl-2/Bax ratio is ≥ 2.0 were alive after 36 months and survived without any evidence of disease for 24 months (Bcl-2/Bax ≥ 2.0 versus Bcl-2/Bax < 2.0; P = .035, n = 61 in OS, P < .001, n = 76 in DFS, respectively). In 56 patients who received immunochemoradiotherapy using UFT and OK-432 in combination with radiotherapy, a statistically significant relationship between the Bcl-2/Bax ratio and the therapeutic effect estimated using Response Evaluation Criteria in Solid Tumors was observed, as well as a relation with interferon-γ (IFN-γ) induction in response to the therapy [P = .002 in complete response versus partial response + stable disease; P = .046 in IFN-γ(+) versus IFN-γ(-)]. In addition, there were significant correlations of the Bcl-2/Bax ratio with both the absolute number of CD4+ T cells and the rate of CD4+ T cell and natural killer cell activity. These findings strongly suggest that the balance of expression of Bcl-2 and Bax genes in circulating immune cells has a high prognostic value in head and neck cancer patients.